Toxicity of a Novel Herbomineral Preparation Las01 on Human Cancer Cell Lines and Its Safety Profile in Humans and Animals. (30th August 2012) - Sheikh, Saba; Srivastava, Ashok; Tripathi, Rajesh; Tripathi, Shalini; Trivedi, V. P.; Saxena, R. C.
Abstract : Polyhedral formulations based on Rasayana therapy described in Charaka Samhita showed remarkable improvement in quality of life of various cancer patients who have been found to be refractory or poor responders to modern chemotherapy and radiation treatment. One of the most recent novel herbomineral preparation, Las01 prepared absolutely as per the instruction given in the ancient Ayurvedic literature has been found to be effective as a potent anticancer drug in the human cell lines, the MCF-7 and Hela cancer cell lines. This novel preparation of Las01 is also found to be devoid of toxicity both in animals as well as in human subjects, which is the main drawback of chemotherapeutic agents used in modern system of medicine. Our results warrant multicentric clinical trials on a large scale which seems to be a future promising drug to cure incurables cancer patients.